Effect of Different Treatment on the Adsorption of p-Cresol by Activated Carbon (Langmuir Isotherm) - Nouri, Sirous (Asian Journal of Chemistry, 2010)
Adsorption of p-cresol by four activated carbons (one untreated and three treated) was carried out at 301 K and at controlled pH conditions. In acidic conditions such that pH of solution is well below the pKa of p-cresol (molecular form), it was observed that the adsorbate solubility and the electron density of aromatic ring and also those of the carbon surface, are the main forces involved in the adsorption process, by affecting the extent of London dispersion forces. In higher solution pH conditions (in ionic form), on the other hand, it was found that the electrostatic forces played a significant role on the extent of adsorption. The effect of pH must be considered from its combined effects on the carbon surface and on the solute molecules. It was found that the uptake of the molecular form of the aromatic solute was dependent on the substituents of the aromatic ring. Adsorption of the solute in higher pH values was found to be dependent on the concentration of anionic form of the solute. All isotherms were fitted into Langmuir isotherm equations to find the relative factors.